2016
DOI: 10.3390/ma9040215
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Silver Chloride Nanoparticles Stabilized with Chitosan Oligomer for the Healing of Burns

Abstract: Recently, numerous compounds have been studied in order to develop antibacterial agents, which can prevent colonized wounds from infection, and assist the wound healing. For this purpose, novel silver chloride nanoparticles stabilized with chitosan oligomer (CHI-AgCl NPs) were synthesized to investigate the influence of antibacterial chitosan oligomer (CHI) exerted by the silver chloride nanoparticles (AgCl NPs) on burn wound healing in a rat model. The CHI-AgCl NPs had a spherical morphology with a mean diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…The crystalline nature of Ag/AgCl‐NPs and the presence of silver and silver chloride were confirmed by XRD. The formation of AgCl‐NPs was explained by Kang et al who revealed that synthesis of AgCl‐NPs from oligomeric chitosan occurred in two steps 26 . At first, Ag ions readily reacted with Cl ions and the amino and hydroxyl groups stabilized the AgCl‐NPs.…”
Section: Discussionmentioning
confidence: 99%
“…The crystalline nature of Ag/AgCl‐NPs and the presence of silver and silver chloride were confirmed by XRD. The formation of AgCl‐NPs was explained by Kang et al who revealed that synthesis of AgCl‐NPs from oligomeric chitosan occurred in two steps 26 . At first, Ag ions readily reacted with Cl ions and the amino and hydroxyl groups stabilized the AgCl‐NPs.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that Ag/ AgCl-NPs interact with the actin cytoskeleton, causing structural and functional damage to cytoskeletal elements (Urbańska et al 2015). In addition, the active surface of AgNPs can directly induce the generation of free radicals and the dissolution of AgNPs into Ag ions, which is a characteristic shared by silver-based nanoparticles, including Ag/AgCl-NPs (Kang et al 2016). Ag ions damage the DNA and disrupt of the mitochondrial membrane potential, leading to the release of cytochrome c and to mitochondrial-dependent apoptosis (Hsin et al 2008;Piao et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, metal-chitosan (Me-CS) composites have many fascinating applications in catalysis, biosensors and biomaterials [ 24 , 25 ]. A number of studies have been issued on CS combination with different inorganic nanostructures, such as Pd [ 26 , 27 ], Au [ 28 , 29 , 30 , 31 , 32 ], Ag and its compounds [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], Pt [ 27 , 41 ], Fe and its oxides [ 42 , 43 , 44 ], ZnO [ 20 , 45 , 46 ], zeolite [ 47 ], silica [ 48 ] and graphene [ 49 ], just to cite a few. The inclusion of copper nanophases in CS matrix is quite diffused, as well [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%